Copyright (c) 1989 Association of Mizar Users
environ vocabulary VECTSP_1, RLVECT_1, ARYTM_1, RELAT_1, BINOP_1, FUNCT_1, MCART_1, PARSP_1; notation TARSKI, XBOOLE_0, ZFMISC_1, SUBSET_1, MCART_1, DOMAIN_1, FUNCT_2, BINOP_1, STRUCT_0, RLVECT_1, VECTSP_1; constructors DOMAIN_1, BINOP_1, VECTSP_1, MEMBERED, XBOOLE_0; clusters STRUCT_0, SUBSET_1, VECTSP_1, MEMBERED, ZFMISC_1, XBOOLE_0; requirements SUBSET, BOOLE; definitions TARSKI, STRUCT_0; theorems MCART_1, VECTSP_1, BINOP_1, FUNCT_2, TARSKI, RLVECT_1; schemes BINOP_1, FUNCT_2, XBOOLE_0; begin reserve F for Field, a,b,c,d,e,f,g,h for Element of F; Lm1: for F being add-associative right_zeroed right_complementable (non empty LoopStr), a, b being Element of F holds -(a-b) = b-a proof let F be add-associative right_zeroed right_complementable (non empty LoopStr), a, b be Element of F; thus -(a-b) = b+-a by RLVECT_1:47 .= b-a by RLVECT_1:def 11; end; Lm2: (a-b)*(c-d) - (b-a)*(d-c) = 0.F proof -(a-b) = b-a & -(c-d) = d-c by Lm1; then (a-b)*(c-d)-(b-a)*(d-c)=(a-b)*(c-d)-((a-b)*(c-d)) by VECTSP_1:42; hence thesis by RLVECT_1:28; end; Lm3: a*(b-b) - (c-c)*d = 0.F proof b-b = 0.F & c-c = 0.F by RLVECT_1:28; then a*(b-b) = 0.F & (c-c)*d = 0.F by VECTSP_1:39; hence thesis by RLVECT_1:28; end; Lm4: a <> 0.F & a*e - d*b = 0.F & a*c - h*b = 0.F implies d*c - h*e = 0.F proof assume a <> 0.F & a*e - d*b = 0.F & a*c - h*b = 0.F; then e = d*b*a" & c = h*b*a" by VECTSP_1:88; then e = d*(b*a") & c = h*(b*a") by VECTSP_1:def 16; then h*e = (h*d)*(b*a") & d*c = (d*h)*(b*a") & d*h =h*d by VECTSP_1:def 16; hence d*c - h*e = 0.F by RLVECT_1:28; end; Lm5: a*b - c*d = 0.F implies d*c - b*a = 0.F proof assume a*b - c*d = 0.F; then A1: -(a*b - c*d) = 0.F by RLVECT_1:25; thus d*c - b*a = d*c + -(b*a) by RLVECT_1:def 11 .= 0.F by A1,RLVECT_1:47; end; Lm6: b <> 0.F & a*e - d*b = 0.F & a*c - h*b = 0.F implies d*c - h*e = 0.F proof assume b <> 0.F; then b*d - e*a = 0.F & b*h - c*a = 0.F implies e*h - c*d = 0.F by Lm4; hence thesis by Lm5; end; Lm7: (c*d)*(a*b) = ((a*c)*d)*b proof thus (c*d)*(a*b) = (a*(c*d))*b by VECTSP_1:def 16 .= ((a*c)*d)*b by VECTSP_1:def 16; end; Lm8: a*b - c*d = 0.F implies (a*f*g*b) - (c*f*g*d) = 0.F proof assume A1: a*b - c*d = 0.F; (a*f*g*b) = (f*g)*(a*b) & (c*f*g*d) = (f*g)*(c*d) by Lm7; hence (a*f*g*b) - (c*f*g*d) = (f*g)*(a*b - c*d) by VECTSP_1:43 .= 0.F by A1,VECTSP_1:39; end; Lm9: (a-b)*(c-d) = a*c + (-a*d +-(b*(c-d))) proof thus (a-b)*(c-d) = (a+-b)*(c-d) by RLVECT_1:def 11 .= a*(c-d)+(-b)*(c-d) by VECTSP_1:def 18 .= a*(c-d)+-b*(c-d) by VECTSP_1:41 .= (a*c-a*d)+-b*(c-d) by VECTSP_1:43 .= (a*c+-a*d)+-b*(c-d) by RLVECT_1:def 11 .= a*c + (-a*d +-(b*(c-d))) by RLVECT_1:def 6; end; Lm10: (a+b)+(c+d) = a+(b+c)+d proof thus (a+b)+(c+d) = (a+b)+c+d by RLVECT_1:def 6 .= a+(b+c)+d by RLVECT_1:def 6; end; Lm11: for F being add-associative right_zeroed right_complementable (non empty LoopStr), a, b, c being Element of F holds (b+a)-(c+a) = b-c proof let F be add-associative right_zeroed right_complementable (non empty LoopStr), a,b,c be Element of F; thus (b+a)-(c+a) = (b+a)+-(c+a) by RLVECT_1:def 11 .= (b+a)+(-a+-c) by RLVECT_1:45 .= ((b+a)+-a)+-c by RLVECT_1:def 6 .= (b+(a+-a))+-c by RLVECT_1:def 6 .= (b+0.F)+-c by RLVECT_1:def 10 .= b+-c by RLVECT_1:10 .= b-c by RLVECT_1:def 11; end; Lm12: for F being add-associative right_zeroed right_complementable (non empty LoopStr), a, b being Element of F holds a + b = -(-b + -a) proof let F be add-associative right_zeroed right_complementable (non empty LoopStr), a,b be Element of F; thus a + b = --(a + b) by RLVECT_1:30 .= -(-b + -a) by RLVECT_1:45; end; Lm13: (a-b)*(c-d)-(a-e)*(c-f) = 0.F implies (b-a)*(f-d)-(b-e)*(f-c) = 0.F proof assume A1: (a-b)*(c-d)-(a-e)*(c-f) = 0.F; A2: (a-b)*(c-d) = a*c+(-a*d+-(b*(c-d))) & (a-e)*(c-f) = a*c+(-a*f+-(e*(c-f))) by Lm9; (b-a)*(f-d) = b*f+(-b*d+-(a*(f-d))) & (b-e)*(f-c) = b*f +(-b*c+-(e*(f-c))) by Lm9; hence (b-a)*(f-d)-(b-e)*(f-c) = (-b*d+-(a*(f-d)))-(-b*c+-(e*(f-c))) by Lm11 .= (-b*d+-(a*f-a*d))-(-b*c+-(e*(f-c))) by VECTSP_1:43 .= (-b*d+(-a*f+a*d))-(-b*c+-(e*(f-c))) by RLVECT_1:47 .= ((-b*d+a*d)+-a*f)-(-b*c+-(e*(f-c))) by RLVECT_1:def 6 .= ((a*d+-b*d)+-a*f)+-(-b*c+-(e*(f-c))) by RLVECT_1:def 11 .= ((a*d+-b*d)+-a*f)+(--b*c+--(e*(f-c))) by RLVECT_1:45 .= ((a*d+-b*d)+-a*f)+(b*c+--(e*(f-c))) by RLVECT_1:30 .= ((a*d+-b*d)+-a*f)+(b*c+(e*(f-c))) by RLVECT_1:30 .= ((a*d+-b*d)+(-a*f+b*c))+(e*(f-c)) by Lm10 .= ((a*d+-b*d)+b*c)+(-a*f+(e*(f-c))) by Lm10 .= (a*d+(-b*d+b*c))+(-a*f+(e*(f-c))) by RLVECT_1:def 6 .= (a*d+(b*c-b*d))+(-a*f+(e*(f-c))) by RLVECT_1:def 11 .= (a*d+b*(c-d))+(-a*f+(e*(f-c))) by VECTSP_1:43 .= -(-a*d+-b*(c-d))+(-a*f+(e*(f-c))) by Lm12 .= -(-a*d+-b*(c-d))+-(--a*f+-(e*(f-c))) by Lm12 .= -(-a*d+-b*(c-d))+-(a*f+-(e*(f-c))) by RLVECT_1:30 .= -((-a*d+-b*(c-d))+(a*f+-(e*(f-c)))) by RLVECT_1:45 .= -((-a*d+-b*(c-d))+-(-a*f+--(e*(f-c)))) by Lm12 .= -((-a*d+-b*(c-d))-(-a*f+--(e*(f-c)))) by RLVECT_1:def 11 .= -((-a*d+-b*(c-d))-(-a*f+-((-(f-c))*e))) by VECTSP_1:41 .= -((-a*d+-b*(c-d))-(-a*f+-(e*(c-f)))) by Lm1 .= - 0.F by A1,A2,Lm11 .= 0.F by RLVECT_1:25; end; Lm14: a-(a+b+-c) = c-b proof thus a-(a+b+-c) = a-(a+(b+-c)) by RLVECT_1:def 6 .= a-(a+(b-c)) by RLVECT_1:def 11 .= a+-(a+(b-c)) by RLVECT_1:def 11 .= a+(-a+-(b-c)) by RLVECT_1:45 .= (a+-a)+-(b-c) by RLVECT_1:def 6 .= 0.F + -(b-c) by RLVECT_1:def 10 .= -(b-c) by RLVECT_1:10 .= c-b by Lm1; end; Lm15: (a-b)*(c-(c+h+-g))-(e-(e+b+-a))*(g-h) = 0.F proof c-(c+h+-g) = g-h & e-(e+b+-a) = a-b by Lm14; hence thesis by RLVECT_1:28; end; :: :: 1. A THREE-DIMENSION CARTESIAN GROUP :: reserve x,y for Element of [:the carrier of F,the carrier of F,the carrier of F:]; deffunc 3F(Field) = [:the carrier of $1,the carrier of $1,the carrier of $1:]; definition let F; func c3add(F) -> BinOp of [:the carrier of F,the carrier of F,the carrier of F:] means :Def1: it.(x,y) = [x`1+y`1,x`2+y`2,x`3+y`3]; existence proof deffunc O(Element of 3F(F),Element of 3F(F)) = [$1`1+$2`1,$1`2+$2`2,$1`3+$2`3]; consider f be BinOp of 3F(F) such that A1: f.(x,y) = O(x,y) from BinOpLambda; take f; thus thesis by A1; end; uniqueness proof let f,g be BinOp of 3F(F) such that A2: f.(x,y) = [x`1+y`1,x`2+y`2,x`3+y`3] and A3: g.(x,y) = [x`1+y`1,x`2+y`2,x`3+y`3]; f.(x,y) = g.(x,y) proof thus f.(x,y)=[x`1+y`1,x`2+y`2,x`3+y`3] by A2 .= g.(x,y) by A3; end; hence f = g by BINOP_1:2; end; end; definition let F,x,y; func x+y -> Element of [:the carrier of F,the carrier of F,the carrier of F:] equals :Def2: (c3add(F)).(x,y); coherence; end; canceled 2; theorem Th3: x+y = [x`1+y`1,x`2+y`2,x`3+y`3] proof thus x+y = (c3add(F)).(x,y) by Def2 .= [x`1+y`1,x`2+y`2,x`3+y`3] by Def1; end; theorem Th4: [a,b,c]+[f,g,h]=[a+f,b+g,c+h] proof set abc = [a,b,c] ,fgh = [f,g,h]; abc`1=a & abc`2=b & abc`3=c & fgh`1=f & fgh`2=g & fgh`3=h by MCART_1:47; hence thesis by Th3; end; definition let F; func c3compl(F) -> UnOp of [:the carrier of F,the carrier of F,the carrier of F:] means :Def3: it.(x) = [-x`1,-x`2,-x`3]; existence proof deffunc O(Element of 3F(F)) = [-$1`1,-$1`2,-$1`3]; consider f be UnOp of 3F(F) such that A1: f.(x) = O(x) from LambdaD; take f; thus thesis by A1; end; uniqueness proof let f,g be UnOp of 3F(F) such that A2: f.(x) = [-x`1,-x`2,-x`3] and A3: g.(x) = [-x`1,-x`2,-x`3]; f.(x) = g.(x) proof thus f.(x) = [-x`1,-x`2,-x`3] by A2 .= g.(x) by A3; end; hence f = g by FUNCT_2:113; end; end; definition let F,x; func -x -> Element of [:the carrier of F,the carrier of F,the carrier of F:] equals :Def4: (c3compl(F)).(x); coherence; end; canceled 2; theorem Th7: -x = [-x`1,-x`2,-x`3] proof thus -x = (c3compl(F)).(x) by Def4 .= [-x`1,-x`2,-x`3] by Def3; end; :: :: 2. PARALLELITY STRUCTURE :: reserve S for set; definition let S; mode Relation4 of S -> set means :Def5: it c= [:S,S,S,S:]; existence; end; definition struct(1-sorted) ParStr (# carrier -> set, 4_arg_relation -> Relation4 of the carrier #); end; definition cluster non empty ParStr; existence proof consider A being non empty set, R being Relation4 of A; take ParStr(#A,R#); thus the carrier of ParStr(#A,R#) is non empty; end; end; reserve F for Field; reserve PS for non empty ParStr; definition let PS; let a,b,c,d be Element of PS; pred a,b '||' c,d means :Def6: [a,b,c,d] in the 4_arg_relation of PS; end; definition let F; func C3(F) -> set equals :Def7: [:the carrier of F,the carrier of F,the carrier of F:]; coherence; end; definition let F; cluster C3(F) -> non empty; coherence proof C3(F) = [:the carrier of F,the carrier of F,the carrier of F:] by Def7; hence thesis; end; end; definition let F; func 4C3(F) -> set equals :Def8: [:C3(F),C3(F),C3(F),C3(F):]; coherence; end; definition let F; cluster 4C3(F) -> non empty; coherence proof 4C3 F = [:C3(F),C3(F),C3(F),C3(F):] by Def8; hence thesis; end; end; reserve x for set, a,b,c,d,e,f,g,h,i,j,k,l for Element of [:the carrier of F,the carrier of F,the carrier of F:]; definition let F; func PRs(F) -> set means :Def9: x in it iff x in 4C3(F) & ex a,b,c,d st x = [a,b,c,d] & (a`1-b`1)*(c`2-d`2) - (c`1-d`1)*(a`2-b`2) = 0.F & (a`1-b`1)*(c`3-d`3) - (c`1-d`1)*(a`3-b`3) = 0.F & (a`2-b`2)*(c`3-d`3) - (c`2-d`2)*(a`3-b`3) = 0.F; existence proof defpred P[set] means ex a,b,c,d st $1 = [a,b,c,d] & (a`1-b`1)*(c`2-d`2) - (c`1-d`1)*(a`2-b`2) = 0.F & (a`1-b`1)*(c`3-d`3) - (c`1-d`1)*(a`3-b`3) = 0.F & (a`2-b`2)*(c`3-d`3) - (c`2-d`2)*(a`3-b`3) = 0.F; thus ex X be set st for x be set holds x in X iff x in 4C3(F) & P[x] from Separation; end; uniqueness proof defpred CB[set] means $1 in 4C3(F) & ex a,b,c,d st $1 = [a,b,c,d] & (a`1-b`1)*(c`2-d`2) - (c`1-d`1)*(a`2-b`2) = 0.F & (a`1-b`1)*(c`3-d`3) - (c`1-d`1)*(a`3-b`3) = 0.F & (a`2-b`2)*(c`3-d`3) - (c`2-d`2)*(a`3-b`3) = 0.F; let H1,H2 be set such that A1: x in H1 iff CB[x] and A2: x in H2 iff CB[x]; x in H1 iff x in H2 proof x in H1 iff CB[x] by A1; hence thesis by A2; end; hence H1 = H2 by TARSKI:2; end; end; canceled 5; theorem Th13: PRs(F) c= [:C3(F),C3(F),C3(F),C3(F):] proof let x; 4C3(F) = [:C3(F),C3(F),C3(F),C3(F):] by Def8; hence thesis by Def9; end; definition let F; func PR(F) -> Relation4 of C3(F) equals :Def10: PRs(F); coherence proof PRs(F) c= [:C3(F),C3(F),C3(F),C3(F):] by Th13; hence thesis by Def5; end; end; definition let F; func MPS(F) -> ParStr equals :Def11: ParStr (# C3(F),PR(F) #); correctness; end; definition let F; cluster MPS(F) -> strict non empty; coherence proof MPS(F) = ParStr (# C3(F),PR(F) #) by Def11; hence MPS F is strict & the carrier of MPS F is non empty; end; end; canceled 2; theorem Th16: the carrier of MPS(F) = C3(F) proof MPS(F) = ParStr (# C3(F),PR(F) #) by Def11; hence thesis; end; theorem Th17: the 4_arg_relation of MPS(F) = PR(F) proof MPS(F) = ParStr (# C3(F),PR(F) #) by Def11; hence thesis; end; reserve a,b,c,d,p,q,r,s for Element of MPS(F); theorem Th18: a,b '||' c,d iff [a,b,c,d] in PR(F) proof the 4_arg_relation of MPS(F) = PR(F) by Th17; hence thesis by Def6; end; theorem Th19: [a,b,c,d] in PR(F) iff ([a,b,c,d] in 4C3(F) & ex e,f,g,h st [a,b,c,d] = [e,f,g,h] & (e`1-f`1)*(g`2-h`2) - (g`1-h`1)*(e`2-f`2) = 0.F & (e`1-f`1)*(g`3-h`3) - (g`1-h`1)*(e`3-f`3) = 0.F & (e`2-f`2)*(g`3-h`3) - (g`2-h`2)*(e`3-f`3) = 0.F) proof PR(F) = PRs(F) by Def10; hence thesis by Def9; end; theorem Th20: a,b '||' c,d iff ([a,b,c,d] in 4C3(F) & ex e,f,g,h st [a,b,c,d] = [e,f,g,h] & (e`1-f`1)*(g`2-h`2) - (g`1-h`1)*(e`2-f`2) = 0.F & (e`1-f`1)*(g`3-h`3) - (g`1-h`1)*(e`3-f`3) = 0.F & (e`2-f`2)*(g`3-h`3) - (g`2-h`2)*(e`3-f`3) = 0.F) proof a,b '||' c,d iff [a,b,c,d] in PR(F) by Th18; hence thesis by Th19; end ; theorem Th21: the carrier of MPS(F) = [:the carrier of F,the carrier of F,the carrier of F:] proof 3F(F) = C3(F) by Def7; hence thesis by Th16; end; theorem Th22: [a,b,c,d] in 4C3(F) proof the carrier of MPS(F) = C3(F) & 4C3(F) = [:C3(F),C3(F),C3(F),C3(F):] by Def8,Th16; hence thesis; end; theorem Th23: a,b '||' c,d iff ex e,f,g,h st [a,b,c,d] = [e,f,g,h] & (e`1-f`1)*(g`2-h`2) - (g`1-h`1)*(e`2-f`2) = 0.F & (e`1-f`1)*(g`3-h`3) - (g`1-h`1)*(e`3-f`3) = 0.F & (e`2-f`2)*(g`3-h`3) - (g`2-h`2)*(e`3-f`3) = 0.F proof [a,b,c,d] in 4C3(F) by Th22; hence thesis by Th20; end; theorem Th24: a,b '||' b,a proof the carrier of MPS(F) = 3F(F) by Th21; then consider e,f such that A1: [e,f,f,e] = [a,b,b,a]; (e`1-f`1)*(f`2-e`2) - (f`1-e`1)*(e`2-f`2) = 0.F & (e`1-f`1)*(f`3-e`3) - (f`1-e`1)*(e`3-f`3) = 0.F & (e`2-f`2)*(f`3-e`3) - (f`2-e`2)*(e`3-f`3) = 0.F by Lm2; hence thesis by A1,Th23; end; theorem Th25: a,b '||' c,c proof the carrier of MPS(F) = 3F(F) by Th21; then consider e,f,g such that A1: [e,f,g,g] = [a,b,c,c]; (e`1-f`1)*(g`2-g`2) - (g`1-g`1)*(e`2-f`2) = 0.F & (e`1-f`1)*(g`3-g`3) - (g`1-g`1)*(e`3-f`3) = 0.F & (e`2-f`2)*(g`3-g`3) - (g`2-g`2)*(e`3-f`3) = 0.F by Lm3; hence thesis by A1,Th23; end; theorem Th26: a,b '||' p,q & a,b '||' r,s implies p,q '||' r,s or a=b proof defpred CB[(Element of 3F(F)),(Element of 3F(F)), (Element of 3F(F)),Element of 3F(F)] means ($1`1-$2`1)*($3`2-$4`2) - ($3`1-$4`1)*($1`2-$2`2) = 0.F & ($1`1-$2`1)*($3`3-$4`3) - ($3`1-$4`1)*($1`3-$2`3) = 0.F & ($1`2-$2`2)*($3`3-$4`3) - ($3`2-$4`2)*($1`3-$2`3) = 0.F; assume A1: a,b '||' p,q & a,b '||' r,s; then consider e,f,g,h such that A2: [e,f,g,h] = [a,b,p,q] and A3: CB[e,f,g,h] by Th23; consider i,j,k,l such that A4: [i,j,k,l] = [a,b,r,s] and A5: CB[i,j,k,l] by A1,Th23; A6: e = a & f = b & g = p & h = q & i = a & j = b & k = r & l = s by A2,A4,MCART_1:33; set A = e`1-f`1, B = e`2-f`2, C = e`3-f`3, D = g`1-h`1, E = g`2-h`2, K = g`3-h`3, G = k`1-l`1, H = k`2-l`2, I = k`3-l`3; now assume A7: a <> b; now e = [e`1,e`2,e`3] & f = [f`1,f`2,f`3] by MCART_1:48; then A8: e`1 <> f`1 or e`2 <> f`2 or e`3 <> f`3 by A6,A7; per cases by A8,RLVECT_1:35; case A9: A <> 0.F; hence D*H-G*E = 0.F by A3,A5,A6,Lm4; thus A10: D*I-G*K = 0.F by A3,A5,A6,A9,Lm4; E*I = ((D*B)*A")*I & H*K = ((G*B)*A")*K by A3,A5,A6,A9,VECTSP_1:88; hence E*I-H*K = 0.F by A10,Lm8; case A11: B <> 0.F; hence D*H-G*E = 0.F by A3,A5,A6,Lm6; thus A12: E*I-H*K = 0.F by A3,A5,A6,A11,Lm4; D*I = ((E*A)*B")*I & G*K = ((H*A)*B")*K by A3,A5,A6,A11,VECTSP_1:88; hence D*I-G*K = 0.F by A12,Lm8; case A13: C <> 0.F; hence E*I-H*K = 0.F by A3,A5,A6,Lm6; D*H = ((K*A)*C")*H & G*E = ((I*A)*C")*E & K*H - I*E = 0.F by A3,A5,A6,A13,Lm6,VECTSP_1:88; hence D*H-G*E = 0.F by Lm8; thus D*I-G*K = 0.F by A3,A5,A6,A13,Lm6; end; hence ex g,h,k,l st [g,h,k,l] = [p,q,r,s] & CB[g,h,k,l] by A6; end; hence thesis by Th23; end; theorem Th27: a,b '||' a,c implies b,a '||' b,c proof assume a,b '||' a,c; then consider e,f,g,h such that A1: [e,f,g,h] = [a,b,a,c] and A2: (e`1-f`1)*(g`2-h`2) - (g`1-h`1)*(e`2-f`2) = 0.F & (e`1-f`1)*(g`3-h`3) - (g`1-h`1)*(e`3-f`3) = 0.F & (e`2-f`2)*(g`3-h`3) - (g`2-h`2)*(e`3-f`3) = 0.F by Th23; e = a & f = b & g = a & h = c by A1,MCART_1:33; then [f,e,f,h] = [b,a,b,c] & (f`1-e`1)*(f`2-h`2) - (f`1-h`1)*(f`2-e`2) = 0.F & (f`1-e`1)*(f`3-h`3) - (f`1-h`1)*(f`3-e`3) = 0.F & (f`2-e`2)*(f`3-h`3) - (f`2-h`2)*(f`3-e`3) = 0.F by A2,Lm13; hence b,a '||' b,c by Th23; end; theorem Th28: ex d st a,b '||' c,d & a,c '||' b,d proof the carrier of MPS(F) = 3F(F) by Th21; then consider e,f,g such that A1: e = a & f = b & g = c; set h = g+f+-e; reconsider d = h as Element of MPS(F) by Th21; take d; g+f = [g`1+f`1,g`2+f`2,g`3+f`3] & -e = [-e`1,-e`2,-e`3] by Th3,Th7; then h = [g`1+f`1+-e`1,g`2+f`2+-e`2,g`3+f`3+-e`3] by Th4; then A2: h`1 = g`1+f`1+-e`1 & h`2 = g`2+f`2+-e`2 & h`3 = g`3+f`3+(-e`3) by MCART_1:47; then [e,f,g,h] = [a,b,c,d] & (e`1-f`1)*(g`2-h`2) - (g`1-h`1)*(e`2-f`2) = 0.F & (e`1-f`1)*(g`3-h`3) - (g`1-h`1)*(e`3-f`3) = 0.F & (e`2-f`2)*(g`3-h`3) - (g`2-h`2)*(e`3-f`3) = 0.F by A1,Lm15; hence a,b '||' c,d by Th23; [e,g,f,h] = [a,c,b,d] & (e`1-g`1)*(f`2-h`2) - (f`1-h`1)*(e`2-g`2) = 0.F & (e`1-g`1)*(f`3-h`3) - (f`1-h`1)*(e`3-g`3) = 0.F & (e`2-g`2)*(f`3-h`3) - (f`2-h`2)*(e`3-g`3) = 0.F by A1,A2,Lm15; hence thesis by Th23; end; :: :: 3. DEFINITION OF PARALLELITY SPACE :: definition let IT be non empty ParStr; attr IT is ParSp-like means :Def12: for a,b,c,d,p,q,r,s being Element of IT holds a,b '||' b,a & a,b '||' c,c & (a,b '||' p,q & a,b '||' r,s implies p,q '||' r,s or a=b) & (a,b '||' a,c implies b,a '||' b,c) & (ex x being Element of IT st a,b '||' c,x & a,c '||' b,x); end; definition cluster strict ParSp-like (non empty ParStr); existence proof consider F; for a,b,c,d,p,q,r,s being Element of MPS(F) holds a,b '||' b,a & a,b '||' c,c & (a,b '||' p,q & a,b '||' r,s implies p,q '||' r,s or a=b) & (a,b '||' a,c implies b,a '||' b,c) & (ex x being Element of MPS(F) st a,b '||' c,x & a,c '||' b,x) by Th24,Th25,Th26,Th27,Th28; then MPS(F) is ParSp-like by Def12; hence thesis; end; end; definition mode ParSp is ParSp-like (non empty ParStr); end; reserve PS for ParSp, a,b,c,d,p,q,r,s for Element of PS; canceled 6; theorem Th35: a,b '||' a,b proof b,a '||' b,b by Def12; hence a,b '||' a,b by Def12; end; theorem Th36: a,b '||' c,d implies c,d '||' a,b proof assume A1: a,b '||' c,d; a,b '||' a,b by Th35; then a<>b implies c,d '||' a,b by A1,Def12; hence thesis by Def12; end; theorem Th37: a,a '||' b,c proof b,c '||' a,a by Def12; hence a,a '||' b,c by Th36; end; theorem Th38: a,b '||' c,d implies b,a '||' c,d proof assume A1: a,b '||' c,d; a,b '||' b,a by Def12; then a<>b implies b,a '||' c,d by A1,Def12; hence thesis by A1; end; theorem Th39: a,b '||' c,d implies a,b '||' d,c proof assume a,b '||' c,d; then c,d '||' a,b by Th36; then d,c '||' a,b by Th38; hence a,b '||' d,c by Th36; end; theorem Th40: a,b '||' c,d implies b,a '||' c,d & a,b '||' d,c & b,a '||' d,c & c,d '||' a,b & d,c '||' a,b & c,d '||' b,a & d,c '||' b,a proof assume a,b '||' c,d; then c,d '||' a,b by Th36; then A1: d,c '||' a,b by Th38; then A2: d,c '||' b,a by Th39; then c,d '||' b,a by Th38; hence thesis by A1,A2,Th36,Th38; end; theorem Th41: a,b '||' a,c implies a,c '||' a,b & b,a '||' a,c & a,b '||' c,a & a,c '||' b,a & b,a '||' c,a & c,a '||' a,b & c,a '||' b,a & b,a '||' b,c & a,b '||' b,c & b,a '||' c,b & b,c '||' b,a & a,b '||' c,b & c,b '||' b,a & b,c '||' a,b & c,b '||' a,b & c,a '||' c,b & a,c '||' c,b & c,a '||' b,c & a,c '||' b,c & c,b '||' c,a & b,c '||' c,a & c,b '||' a,c & b,c '||' a,c proof assume A1: a,b '||' a,c; then A2: b,a '||' b,c by Def12; a,c '||' a,b by A1,Th36; then c,a '||' c,b by Def12; hence thesis by A1,A2,Th40;end; theorem a=b or c = d or a=c & b=d or a=d & b=c implies a,b '||' c,d by Def12,Th35,Th37; theorem Th43: a<>b & p,q '||' a,b & a,b '||' r,s implies p,q '||' r,s proof assume a<>b & p,q '||' a,b & a,b '||' r,s; then a<>b & a,b '||' p,q & a,b '||' r,s by Th40; hence thesis by Def12; end; theorem not a,b '||' a,c implies a<>b & b<>c & c <>a by Def12,Th35,Th37; theorem not a,b '||' c,d implies a<>b & c <>d by Def12,Th37; canceled; theorem Th47: not a,b '||' a,c implies not a,c '||' a,b & not b,a '||' a,c & not a,b '||' c,a & not a,c '||' b,a & not b,a '||' c,a & not c,a '||' a,b & not c,a '||' b,a & not b,a '||' b,c & not a,b '||' b,c & not b,a '||' c,b & not b,c '||' b,a & not b,a '||' c,b & not c,b '||' b,a & not b,c '||' a,b & not c,b '||' a,b & not c,a '||' c,b & not a,c '||' c,b & not c,a '||' b,c & not a,c '||' b,c & not c,b '||' c,a & not b,c '||' c,a & not c,b '||' a,c & not b,c '||' a,c proof assume A1: not a,b '||' a,c; assume not thesis; then a,c '||' a,b or a,b '||' a,c or a,b '||' a,c or a,c '||' a,b or a,b '||' a,c or a,c '||' a,b or a,c '||' a,b or b,a '||' b,c or b,a '||' b,c or b,a '||' b,c or b,c '||' b,a or b,a '||' b,c or b,c '||' b,a or b,c '||' b,a or b,c '||' b,a or c,a '||' c,b or c,a '||' c,b or c,a '||' c,b or c,a '||' c,b or c,b '||' c,a or c,b '||' c,a or c,b '||' c,a or c,b '||' c,a by Th40; hence contradiction by A1,Th41; end; theorem Th48: not a,b '||' c,d & a,b '||' p,q & c,d '||' r,s & p<>q & r<>s implies not p,q '||' r,s proof assume A1: not a,b '||' c,d & a,b '||' p,q & c,d '||' r,s & p<>q & r<>s; assume p,q '||' r,s; then a,b '||' r,s by A1,Th43; then r,s '||' a,b & r,s '||' c,d by A1,Th40; hence contradiction by A1,Def12; end; theorem Th49: not a,b '||' a,c & a,b '||' p,q & a,c '||' p,r & b,c '||' q,r & p<>q implies not p,q '||' p,r proof assume A1: not a,b '||' a,c & a,b '||' p,q & a,c '||' p,r & b,c '||' q,r & p<>q; now assume p=r; then p,q '||' b,a & p,q '||' b,c by A1,Th40; then b,a '||' b,c by A1,Def12; hence contradiction by A1,Th41; end; hence thesis by A1,Th48; end; theorem Th50: not a,b '||' a,c & a,c '||' p,r & b,c '||' p,r implies p=r proof assume not a,b '||' a,c & a,c '||' p,r & b,c '||' p,r; then not a,c '||' b,c & p,r '||' a,c & p,r '||' b,c by Th40,Th47; hence thesis by Def12; end; theorem Th51: not p,q '||' p,r & p,r '||' p,s & q,r '||' q,s implies r=s proof assume not p,q '||' p,r & p,r '||' p,s & q,r '||' q,s; then not r,p '||' r,q & r,s '||' r,p & r,s '||' r,q by Th47; hence thesis by Def12; end; theorem not a,b '||' a,c & a,b '||' p,q & a,c '||' p,r & a,c '||' p,s & b,c '||' q,r & b,c '||' q,s implies r=s proof assume A1: not a,b '||' a,c & a,b '||' p,q & a,c '||' p,r & a,c '||' p,s & b,c '||' q,r & b,c '||' q,s; then A2: p=q implies p=r & p=s by Th50; now assume p<>q; then not p,q '||' p,r & a<>c & b<>c by A1,Def12,Th35,Th49; then not p,q '||' p,r & p,r '||' p,s & q,r '||' q,s by A1,Def12; hence thesis by Th51; end; hence thesis by A2; end; theorem Th53: a,b '||' a,c & a,b '||' a,d implies a,b '||' c,d proof assume A1: a,b '||' a,c & a,b '||' a,d; now assume a<>b & a<>c; then a<>c & a,c '||' a,d by A1,Def12; then a<>c & a,c '||' c,d by Th41; hence thesis by A1,Th43; end; hence thesis by A1,Th37; end; theorem (for a,b holds a=b) implies for p,q,r,s holds p,q '||' r,s proof assume A1: for a,b holds a=b; let p,q,r,s; r=s by A1; hence thesis by Def12; end; theorem (ex a,b st a<>b & for c holds a,b '||' a,c) implies for p,q,r,s holds p,q '||' r,s proof assume A1: ex a,b st a<>b & for c holds a,b '||' a,c; let p,q,r,s; consider a,b such that A2: a<>b & for c holds a,b '||' a,c by A1; a,b '||' a,p & a,b '||' a,q & a,b '||' a,r & a,b '||' a,s by A2; then a,b '||' p,q & a,b '||' r,s by Th53; hence thesis by A2,Def12; end; theorem not a,b '||' a,c & p<>q implies not p,q '||' p,a or not p,q '||' p,b or not p,q '||' p,c proof assume A1: not a,b '||' a,c & p<>q; assume A2: not thesis; then A3: a<>p by A1,Def12; p,a '||' p,b & p,a '||' p,c by A1,A2,Def12; then a,p '||' a,b & a,p '||' a,c by Th41; hence contradiction by A1,A3,Def12; end;